(3eOi SdWI GdbGVj GdEOGQj aj JhLjg ChGeQ ddEOGQI hGdMdhd eMdgG (B:s (3OQGSI JMdjdjI ebGQfI (B/s - (3MSGe GdOjf QJjH TMGJI WfWGhj,s; (3LGHQ L`GO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2022)
(3Ef OhQ GdbGVj GdEOGQj gh GdHMK Yf fjI GdEOGQI aj JMbjb GdeUdMI GdYGeI hgPG eG jHQQ fTCI GdbVGA GdEOGQj CUdG; aGdOhQ GdGSGSj GdPj jdYHg GdbGVj GdEOGQj gh GdcTa Yf bhGYO GdbGfhf GdEOGQj GdJj jLH Cf jSJfHWgG ef NdGd OhQg aj GdehGRfI Hjf bQGQ GdEOGQI heOi JMbjbg ddUGdM GdYGe gPG ef LgI, hef LgI CNQi VQhQI GdeMGaXI Ydi Mbhb hMQjGJ GdCaQGO aj ehGLgI SdWI GdEOGQI YfO GNJjGQgG JUQakG eYjfkG aj Xd SdWJgG GdJbOjQjI hUhdkG aj GdfgGjI Edi JMbjb GYJHGQGJ GdYOGdI GdefThOI(B. (3aHGJ ef GdeDcO Cf gfGc JQGLYkG MbjbjkG Yf HYV GdeHGOF GdJbdjOjI GdJj cGfJ JMce eSjQI GdbVGA GdEOGQj GdaQfSj QOMG ef GdRef hGdbVGA GdEOGQj GdeUQj, ef NdGd GdYOhd Yf eHOC MXQ JhLjg GdbGVj GdEOGQj ChGeQ ddEOGQI hGdMdhd eMdgG(B. (3hUGQ eHOC MXQ JhLjg ChGeQ ddEOGQI hGdMdhd eMdgG aj bVGA eLdS GdOhdI ShGA aj eUQ Ch aQfSG eLQO acQI fXQjI dG hLhO dgG aj GdhGbY, Hd Ef eLdS GdOhdI GdeUQj bO PgH aj Pdc Edi eOi ChSY ef fXjQg GdaQfSj hMedJ GdcKjQ ef CMcGeg aj cKjQ ef GdCMjGf CekQG hfgkjG ddEOGQI, ceG aj GSJNQGL GdChQGb, Ch JbQjQ GdYah GdUMj ddeMche Ydjge, Ch EKHGJ GdLfSjI, Ch GdJYjjf aj GdhXGFa GdegeI, Ch QO GdCbOejI, heG Edi Pdc, aGdeJCed aj GdCMcGe GdJj CUOQgG eLdS GdOhdI aj bVGjG HWdGf hEdZGA bQGQGJ NUNUI TQcGJ GdbWGY GdYGe, Ch TQcGJ bWGY GdCYeGd GdYGe MedJ aj efWhbgG ChGeQ UQjMI dLgI GdEOGQI HEYGOI GdTQcGJ hEYGOI GdYGedjf ddYed, hHGdJGdj aj Xd gPg GdCMcGe jHbj GdMOjK Yf eHOC MXQ EUOGQ ChGeQ ddEOGQI CeQG dG eYfi dg, ceG Md GdbGVj GdEOGQj eMd LgI GdEOGQI aj eLGd EMdGd GdCSGS ddbGfhfj ddbQGQ, hCSHGHg GdUMjMI eMd GdCSGS Ch GdCSHGH GdHGWdI GdJj GSJfOJ EdjgG LgI GdEOGQI YfO EUOGQ bQGQgG, haj eLGd JMhd GdbQGQGJ GdEOGQjI GdHGWdI Ch GdefYOeI Edi bQGQGJ CNQi UMjMI, haj GdEdZGA GdLRFj ddbQGQ JaGOkjG ddEdZGA Gdcdi dg(B. (3hdYd HGdeeGQSI, CUHM GSJNOGe SdWI GdCeQ TGFYkG LOkG, hbO CTGO HgG GdeJbGVhf GdPjf jQhf ajgG hSjdI aqYGdI dcj jJqe GMJQGe Mbhbge HTcd edehS, ceG QqMHJ Hg GdEOGQI GdJj JJdqbi HPdc GdJaUjd GdJhLjgj ddfJGFL GdefJXQI ef GdbQGQ GdbVGFj, eeG jDcO VQhQI efGTOI GdeTQY HVQhQI hVYg dfUhU EdRGejI JLjR ddbGVj GdEOGQj EUOGQ ChGeQ dLgI GdEOGQI dJMbjb GdgOa GdefThO aj GdhUhd Edi EYGOI JQJjH GdeTQhYjI HUhQI cGedI(B.s
The role of the administrative judge is to search for the administration's intention to achieve the public interest, and this justifies the emergence of the administrative judiciary in the first place. The main role that the administrative judge plays is to reveal the rules of administrative law that he must elicit through his role in balancing the management's decision and the extent to which it achieves this public interest on the one hand, and on the other hand, the need to preserve the rights and freedoms of individuals in the face of the authority of the administration when it chooses a specific action in It remained its discretion in the end to achieve the desired considerations of justice. It has become certain that there has been a real retreat from some of the traditional principles that governed the march of the French administrative judiciary for a long time and the Egyptian administrative judiciary, by abandoning the principle of prohibiting the administrative judge from directing orders to the administration and replacing them. The principle of prohibiting directing orders to the administration and replacing it with the State Council, whether in Egypt or France, became just a theoretical idea that does not exist in reality. As for management, As in the extraction of papers, or the report of a health pardon for the convicts, or proof of nationality, or appointment to important jobs, or the restoration of seniority, etc., the contemplation of the rulings issued by the State Council in cases of nullification and revocation of decisions to privatize public sector companies, or public sector companies Public works carried express orders to the management to return companies and return workers to work, Thus, in light of these provisions, the talk about the principle of prohibiting the issuance of orders to the administration remains meaningless, as the administrative judge has replaced the administration in the field of substituting the legal basis for the decision, and its correct reasons in place of the basis or false reasons that the administration relied upon when issuing its decision, and in the field of Invalid or non-existent administrative decisions are transformed into other valid decisions, and in the partial cancellation of the decision in order to avoid its total cancellation. Perhaps in practice, the use of the power of the order has become very common, and it has been praised by litigants who see it as an effective way to respect their rights in a tangible way. It allows the administrative judge to issue orders to the administration to achieve the desired goal of achieving a complete legal re-arrangeme
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2022.s
(3HHdjhLQGajG(B: (3UaMGJ(B. 384-415.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdbGfhf GdEOGQjs; (3GdbQGQ GdEOGQjs; (3GdSdWI GdJfajPjIs; (3ChGeQ bVGFjIs; (3GdQbGHI GdbVGFjIs; (3bVGA GdGdZGAs; (3LgI GdEOGQIs; (3GdNUheI GdGOGQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdEOGQjs